ANALISIS IMPLEMENTASI KEBIJAKAN HUKUM TERHADAP PENANGANAN KEJAHATAN SIBER DI ERA DIGITAL - Afifah Rizqy Widianingrum (Yayasan Merassa Indonesia Publikasi, 2024)
Cybercrime encompasses a wide range of criminal activities committed through computer networks and the internet, including online fraud, identity theft, malware attacks, hacking, and exploitation of personal data. With the rapid development of information and communication technology, cybercrime has become increasingly complex and widespread, causing adverse impacts on the economy, security, and privacy of individuals. The biggest challenge in handling cybercrime is adapting existing regulations to the evolving dynamics of crime. This paper aims to analyze the implementation of cybercrime handling policies in Indonesia through a sociology of law approach. The implementation of cybercrime policy in Indonesia, especially through the Electronic Information and Transaction Law (UU ITE), involves coordination between various law enforcement agencies and collaboration with the private sector. The case study of personal data theft by a hacker gang in 2022 shows a complex law enforcement process, ranging from case reporting, digital forensic investigation, arrest of perpetrators, to court proceedings. Social, economic, and technological factors, including low digital literacy, rapid technological development, and the technical capacity of law enforcement officers, affect the effectiveness of these policies. This study concludes that improving digital education and literacy, increasing technical capacity and cross-agency cooperation, as well as revising regulations that are responsive to the dynamics of cybercrime, are important steps to improve the effectiveness of cybercrime handling policies in Indonesia.